2004
DOI: 10.1124/jpet.103.062067
|View full text |Cite
|
Sign up to set email alerts
|

Agonist-Induced Serotonin 2A Receptor Desensitization in the Rat Frontal Cortex and Hypothalamus

Abstract: This study examined the time course and possible mechanisms of agonist-induced desensitization of 5-hydroxytryptamine serotonin 2A receptors in the rat frontal cortex and hypothalamic paraventricular nucleus after 1, 4, and 7 days of treatment with (Ϫ)-1-(2,5-dimethoxy-4-iodophenyl)2-aminopropane HCl [(Ϫ)-DOI] (1 mg/kg i.p.), a selective 5-HT 2A/2C receptor agonist. In the frontal cortex, 5-HT-mediated phospholipase C (PLC) enzyme activity decreased by 24 to 30% after 4 to 7 days of (Ϫ)-DOI treatment without a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
20
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 26 publications
4
20
0
Order By: Relevance
“…This observation is consistent with previously published studies (Damjanoska et al, 2004). Sustained agonist treatment decreased DOI-mediated responses, but with the limited number of concentrations of DOI examined and since the dose-response curve did no plateau at the maximal dose of DOI used, we are not able to calculate the Emax and the ED 50 (potency).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This observation is consistent with previously published studies (Damjanoska et al, 2004). Sustained agonist treatment decreased DOI-mediated responses, but with the limited number of concentrations of DOI examined and since the dose-response curve did no plateau at the maximal dose of DOI used, we are not able to calculate the Emax and the ED 50 (potency).…”
Section: Discussionsupporting
confidence: 91%
“…Because down-regulation is one reported mechanism underlying receptor desensitization and in our previous study, we did not observe a decrease G αq and G α11 protein in the PVN (Damjanoska et al, 2004), we hypothesized that the levels of 5-HT 2A receptors in the membrane are reduced in response to sustained treatment with a 5-HT 2A receptor agonist. Surprisingly, we found that 4 or 7 days DOI treatment increased 5-HT 2A receptor protein levels.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…It is well known that chronic treatment with agonists or antagonists of 5-HT 2A receptors typically produces desensitization of 5-HT 2A receptors (Roth et al, 1998;Gray and Roth, 2001;Hanley and Hensler, 2002;Damjanoska et al, 2004). In contrast, withdrawal from cocaine produces supersensitivity of 5-HT 2A receptors (Carrasco et al, 2003;Carrasco et al, 2004b).…”
Section: Discussionmentioning
confidence: 99%
“…These include: (1) increases in 5-HT 2A receptor-mediated neuroendocrine responses, suggesting supersensitivity of postsynaptic 5-HT 2A receptors in PVN (Levy et al, 1992;Baumann et al, 1993;Baumann and Rothman, 1998); and (2) increases in GÎ q and GÎ 11 G-proteins in the membrane fraction of PVN (Carrasco et al, 2003;Carrasco et al, 2004b). Since agonists and antagonists of 5-HT 2A receptors produces desensitization of 5-HT 2A receptors (Gray and Roth, 2001;Hanley and Hensler, 2002;Damjanoska et al, 2004), the increases in 5-HT 2A receptor signaling during withdrawal from cocaine represents a unique adaptive response of this system.…”
Section: Introductionmentioning
confidence: 99%